An Assessment of Histological Margins and Recurrence of Melanoma In Situ. Issue 2 (February 2015) - Joyce, Kenneth M.; Joyce, Cormac W.; Jones, Deirdre M.; Donnellan, Paul; Hussey, Alan J.; Regan, Padraic J.; Kelly, Jack L.
Abstract : Background: Melanoma in situ (MIS) accounts for up to 27% of all melanomas. MIS has no metastatic potential and the aim should be to excise the lesion completely with a clear histological margin, although margin clearance remains undefined. We aimed to assess the relation of histological excision margins of MIS to recurrence and progression to invasive disease. Methods: We analyzed all patients with MIS excised by wide local excision or staged excision in our institution over a 5-year period from December 2008 to January 2014 using a prospectively maintained database. Clinicopathologic details included patient demographics, anatomical site of lesion, melanoma subtype, histological excision margin, and recurrence. Results: A total of 410 patients had MIS excised during this time, the majority of which were lentigo maligna subtype (79%). The average histological excision margin was 3.7 mm. The rate of recurrence was 2.2% (9/410), with a median follow-up of 23 months. Lentigo maligna had a similar rate of recurrence to non-lentigo MIS (2.3% vs 1.2%) ( P = 0.69). The mean excision margin of those that recurred was 1.9 mm compared with an average of 3.8 mm in those that did not. The rate of recurrence of MIS with histological excision margin ⩽3.00 mm was 3.8% compared with 0.5% in those with a histological margin >3.00 mm ( P = 0.03). One case of MIS recurred as invasive disease. Conclusion: At institutions using wide local excision or staged excision for MIS, a histological margin of >3.0 mm is required to achieve a low recurrence rate.